Self-management interventions for cancer survivors: a systematic review - Connolly, Deirdre; Boland, Lauren (My University, 2018)
Purpose: Many cancer survivors experience problems with persisting symptoms such as pain, fatigue, anxiety and depression post-treatment. Self-management interventions are recommended for cancer patients as they can help individuals identify and manage these continuing symptoms. This systematic review examines the type, content and impact of self-management inter- ventions for cancer survivors on health outcomes such as activity participation, self-efficacy, quality of life and symptom management. Methods: This was a systematic review of the English language scientific literature searched for randomised controlled trials (RCT), systematic reviews and meta-analyses of self-management programmes conducted with cancer survivors. Six databases were systematically searched. Results Initial searches yielded 2633 citations. Following screening and a risk of bias assessment, six studies were included in the final review. Heterogeneity of the interventions precluded meta-analysis. Three studies reported significant differences between groups in a number of areas including fatigue, physical functioning, distress and self-efficacy at their first follow-up assessment. These studies included two psychosocial interventions and one exercise and diet intervention. Not all findings were sustained across studies at follow-up assessment. Conclusion: It is not possible to draw definitive conclusions as to the impact the different types of self-management programme had on cancer survivors. The sustainability of the interventions reviewed was poor, suggesting that cancer survivors require interventions that can be applied into their daily activities.
PUBLISHED
Keywords: Self-management, Cancer survivors, Systematic review; Cancer; Chronic Illness self-management; Health outcomes; Self-Management; Chronic Health Condition; Health